Stages of Engineering a (Really) New Microbicidal Medical Device. (Knovel, 2012)
Describing the decade long drive to develop a microbicidal bandage of treated cellulose, from initial material discovery through testing and trials to FDA approval and market launch. "Gauze treated in this manner had an immobilized polyquaternary ammonium polymer attached that killed bacteria quickly on contact and did so in the presence of wound exudate fluids." -- from the text.